17 Subclassification of recreational runners with a running-related injury based on running kinematics measured with two-dimensional video analysis. (April 2019) - Dingenen, Bart; Staes, Filip; Vanelderen, Romy; Ceyssens, Linde; Malliaras, Peter; Barton, Christian; Deschamps, Kevin
Abstract : Introduction: The aim of this study was to explore whether homogeneous subgroups could be classified within the running kinematics of a group of recreational runners with a running-related injury (RRI). Materials and methods: Fifty-three recreational runners (15 males, 38 females) with an RRI ran on a treadmill at preferred speed. Digital videos were recorded in the frontal and sagittal plane with two iPads. Outcome measures included foot and tibia inclination at initial contact, and hip adduction and knee flexion during midstance. All angles were manually drawn using Kinovea and an average of seven consecutive steps was calculated for each angle. The four outcome measures were clustered using K-means cluster analysis (n=2–10). Silhouette coefficients were used to detect optimal clustering. Results: The cluster analysis led to the classification of two distinct subgroups (mean silhouette coefficient=0.53). Cluster 1 (n=39) was characterized by higher foot inclination and tibia inclination at initial contact, higher knee flexion during midstance, and lower hip adduction during midstance compared to cluster 2 (n=14). Fifteen out of 17 (88%) shin injuries were classified in cluster 1. Other injuries were more divided over both clusters. The ratio males/females was higher in cluster 1 (44%) versus cluster 2 (27%). Conclusion: This is the first study to classify subgroup profiles of running kinematics in recreational runners with an RRI based on two-dimensional video analysis. Two distinct subgroups were identified. This subclassification can help clinicians in their clinical reasoning process when evaluating kinematics of runners with an RRI and developing targeted gait-retraining strategies.